Optimalisasi Keterampilan Sosial Anak Melalui Make A Match Pada Anak Usia 5-6 Tahun) - Nurul Hadidah Al-Hadid; Masganti Sit (Prodi Pendidikan Islam Anak Usia Dini Sekolah Tinggi Agama Islam Negeri Mandailing Natal- Sumatera Utara, 2026)
This study aims to optimize the social skills of children aged 5–6 years through the implementation of the Make A Match learning model in Classroom Action Research (CAR) at RA Al-Ikhlashiyah 2 . Social skills are an essential aspect of early childhood development, particularly in terms of cooperation, communication, and active participation in group activities. The research employed a Classroom Action Research design based on the Kemmis and McTaggart model, which consists of planning, action, observation, and reflection cycles. The subjects of the study were 10 children in Group A aged 5–6 years. Data were collected through observation sheets, performance assessments, and documentation, and analyzed using descriptive quantitative and qualitative techniques. The findings revealed a significant improvement in children’s social skills across the research cycles. In the pre-action stage, only 30% of children reached the expected development category. After implementing the Make A Match model in Cycle I, the achievement increased to 60%, and further improved to 90% in Cycle II, exceeding the success indicator of 80%. The improvement was marked by increased communication, cooperation, empathy, and active participation during learning activities. In conclusion, the Make A Match learning model is effective in optimizing the social skills of early childhood learners by providing interactive, collaborative, and enjoyable learning experiences. This model can be recommended as an alternative instructional strategy for teachers in early childhood education to enhance children’s social development.